Information overload and knowledge deficit: an imbalance “harmful to health” - Añel Rodríguez, Rosa María (Revista Española de Comunicación en Salud, 2022)
The impact of the media on public opinion and the ease of access to information, thanks to the Internet and new technologies, have displaced health professionals as the main source of health information. Citizens' expectations regarding the health system have also changed at the same time as the doctor-patient relationship, with the patient emerging as a more informed, consumer and demanding agent. We analyze the factors that have led to the current situation of prestige mistrust and loss of those who should never have ceased to be the health information main sources: health professionals and organizations, in collaboration with the media and information professionals.
Keywords: health; health education; mass media; infodemic; primary care; public health